A review of Chilean chiggers (Acari: Trombiculidae), with the description of a new genus and ten new species - Stekolnikov, Alexandr A.; González-Acuña, Daniel (Zootaxa, 2015)
A new genus and species of chigger mites, Diaguitacarus choapensis gen. et sp. nov., is described from four lizard species of the genus Liolaemus in Choapa Province of Chile. Eight new chigger species are described from lizards of the genera Liolaemus, Phymaturus (Squamata: Liolaemidae), and Microlophus (Squamata: Tropiduridae), in Arica and Parinacota, Atacama, Coquimbo, Valparaíso, and Biobío Regions: Eutrombicula nerudai sp. nov., Eutrombicula mistrali sp. nov., Eutrombicula picunche sp. nov., Microtrombicula mapuche sp. nov., Parasecia molini sp. nov., Paratrombicula philippii sp. nov., Morelacarus jorgei sp. nov., and Morelacarus camanchaca sp. nov. A new species Proschoengastia antarctica sp. nov., which is described from American mink Neovison vison on Navarino Island (Region of Magallanes and Antártica Chilena), is the most southerly chigger species, found at the distance of about 1000 km from the continent of Antarctica. Whartonacarus chaetosus (Brennan and Jones, 1961) comb. nov., which was described from Peru, is for the first time recorded in Chile (Atacama Region) and on Microlophus atacamensis. A new combination Proschoengastia macrochaeta (Brennan and Jones, 1961) comb. nov. is established. The genus Morelacarus Vercammen-Grandjean, 1973 previously known from Mexico and southwestern USA is for the first time recorded in Chile. A review of all previously described Chilean chiggers and a key to Eutrombicula species from Chile are provided. In all, 22 species from 13 genera were recorded in Chile, of which only one species (Whartonacarus chaetosus) is known outside the country.